ANALYSIS OF WORKING TIME OF WOMEN TEA HARVESTERS AT SMM Co - Pranata, Evan; Yuliarso, M.Zulkarnain; Badrudin, Redy (Journal of Agri Socio Economics and Business, 2024)
Sarana Mandiri Mukti Corporation’s tea harvesting mothers are driven by the family's economic situation. Women tea harvesters (domestic work) support their families financially in addition to being housewives. Tea plucking housewives come from diverse locations near the tea estates. Harvesters' daily activities fall into four categories: productive, home, social, and rest. The purpose of this study is to assess the working hours of female tea harvesters and the factors that impact them. The descriptive technique was the primary methodology employed in this study. Multiple Linear Regression is a technique for data analysis. According to research data, tea harvesters often labor nine hours every day. Women who harvest tea can spend nine hours per day (37.5%) on productive activities, three hours on homework (12.5%), four hours on social events (16.67%), and eight hours resting (33.33%). Tea Picker Revenue (X1TPR), Number of Family Dependents (X3NFD), Age (X4AGE), Education Level (X5EDL), and employment Experience (X6EXP) all impact the length of employment of female tea harvesters. Partially Tea Picker Revenue (X1TPR), Total Family Revenue (X2TFR), Number of Family Dependents (X3NFD), Age (X4AGE), and Education Level (X5EDL), but Total Family Income (X2TFR) and Work Experience (X6EXP) have no effect on the work of female tea harvesters.